Estudo do balanço de água para o Cultivo de Soja sob dois Sistemas de Plantio - Moreira, Virnei S.; Timm, Andréa U.; Webler, Geovane; Teichrieb, Cláudio A.; Carneiro, Janaina V.; dos Santos, Daniel M.; Sena, Julio; Gonçalves, Juliana B.; Roberti, Débora R.; Candido, Luiz A.; Fiorin, Jackson E.; Degrazia, Gervásio A.; et al. (Ciência e Natura, 2011)
.